Effects of microstructure on the torsional properties of biodegradable WE43 Mg alloy. (15th August 2020) - Zhang, Yi; Tan, Lili; Wang, Qingchuan; Gao, Ming; Etim, Iniobong P.; Yang, Ke
Abstract: Torsional properties are important performance parameters for bone screw applications, but they are seldom studied, especially for newly developed biodegradable Mg alloys. In this study, WE43 Mg alloy with different microstructures was achieved by equal channel angular pressing (ECAP) and heat treatment, and their torsional properties were studied. In addition, tensile properties were also tested as a comparison. The results indicated that grain refinement led to higher torsional strength and ductility, while the second phases improved the torsional strength but reduced the ductility. The texture was strengthened after ECAP, as a result the tensile strength increased, but the torsional strength did not increase and even decreased, especially for 2-pass ECAP sample with a typical basal fiber texture. The basal plane orientation deviation from the extrusion direction after 4-pass ECAP resulted in higher torsional strength and lower torsional ductility, but lower tensile strength and higher tensile ductility were obtained. This implied that a strong fiber texture would reduce the torsional strength but improve the torsional ductility, which was different from its effect on tensile properties.